Bank Diversification, Competition and Earnings Opacity - Huynh, Japan (Organizations and Markets in Emerging Economies, 2024)
The paper explores the impact of bank diversification on earnings opacity. We aim at offering a comprehensive analysis by focusing on four dimensions of diversification: income, assets, funding, and loan portfolios. Using data from Vietnam over the period 2007–2022, we document consistent and robust evidence that increased diversification across all forms mitigates earnings management via discretionary loan loss provisions. To shed further light on this pattern, we examine how the banking complexity and opacity nexus varies with multiple measures of bank competition. We find that more intense competition in the banking system likely accentuates the impact of diversification on bank earnings manipulations. Our findings provide important implications related to bank business models and banking market structures in the era of financial deregulation and innovation.
Keywords: Bank diversification; Bank opacity; Competition; Loan loss provisions